2021
DOI: 10.1080/09286586.2021.1941127
|View full text |Cite
|
Sign up to set email alerts
|

Population Prevalence of Trachoma in Nine Rural Non-Indigenous Evaluation Units of Brazil

Abstract: Purpose : To assess the contemporary prevalence of trachoma in Brazil’s non-indigenous population, surveys of those thought to be at greatest risk of disease were conducted. Methods : Rural census tracts of non-indigenous population from nine mesoregions were selected to compose the survey evaluation units (EUs) by considering previously endemic municipalities at greatest risk of trachoma. In each of the nine EUs, we conducted a population-based prevalence survey. Every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
2
14
0
1
Order By: Relevance
“…Our results are in line with other trachoma prevalence surveys conducted in Brazil lately, which have shown the decline of trachoma prevalence even in previous endemic areas 7 , 8 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with other trachoma prevalence surveys conducted in Brazil lately, which have shown the decline of trachoma prevalence even in previous endemic areas 7 , 8 .…”
Section: Discussionsupporting
confidence: 92%
“…However, school surveys miss the preschool age group, which is usually the highest risk group for TF 6 . More recent studies have shown a decreasing prevalence, particularly in poor rural areas of Brazil 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the sequelae form of the disease, the TT “ unknown to the health system ,” had an estimated prevalence of 0.22% in some areas, such as northwestern Ceará. This borders the critical value of 0.2% in non-indigenous areas but is within the confidence interval (0.06-0.44) 8 revealed in the National Survey for the Validation of the Elimination of Trachoma as a Public Health Problem, developed by the Ministry of Health, for the period 2018-2019, for non-indigenous areas.…”
Section: Introductionsupporting
confidence: 78%
“…In Brazil, the prevalence of active trachoma is under the limits recommended for eliminating the disease 8 . However, the sequelae form of the disease, the TT “ unknown to the health system ,” had an estimated prevalence of 0.22% in some areas, such as northwestern Ceará.…”
Section: Introductionmentioning
confidence: 99%
“…A etapa 1 do Inquérito para Validação da Eliminação do Tracoma como Problema de Saúde Pública, desenvolvido no Brasil no período de 2018-2019, evidenciou em áreas não indígenas prevalência abaixo de 5% da forma ativa da doença (tracoma folicular) entre crianças de um a nove anos de idade. A forma sequelar da doença (triquíase tracomatosa), desconhecida pelo sistema de saúde, foi inferior ao valor crítico de 0,2%, com exceção a Unidade de Avaliação do Nordeste Cearense, que apresentou prevalência de 0,22% 7 , no entanto, com valor contido no intervalo de confiança.…”
Section: Introductionunclassified